Communication skills of physiotherapy students with patients in outpatient department - Dr. PREETI GAZBARE,; Dr. MANISHA RATHI,; SNEHA SARTAPE, (International Journal of Pharma and Bio Sciences, 2017)
Communication is an activity of conveying information through the exchange of ideas, feelings, attitude, expectations, perceptions or commands by speech-verbal, nonverbal gestures, writings between people. A good therapist must be a good communicator. To assess the communication skills (CS) of physiotherapy students with patients in OPD and to compare the same at Undergraduate (UG) & Postgraduate (PG) level. A cross sectional survey with 100 students from tertiary hospital was randomly selected. And their interaction throughout the treatment was assessed by the assessor via a checklist. Average percentage score of communication skill of all students was 72 %. Student scored highest (78.83%) in history taking and physical examination whereas lowest score (60.75%) in interview initiation. Overall PG students showed better communication skills than the UG students. Among PG’s, history taking & physical examination category scored highest (85%) in communicating with patients whereas in UG’s, interview completion was dealt better with score of 73.37%. Overall 32% students were good and 51% students were fair in communicating with patient in OPD.